2015
DOI: 10.1097/mat.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Hepatitis C Testing in Long-Term LVAD Support

Abstract: Left ventricular assist devices (LVAD) have revolutionized the field of mechanical circulatory support because this technology has been shown to extend life and improve outcomes in patients with advanced heart failure. It has turned out that many LVAD patients become immunologically activated because of serum antibodies directed against human leukocyte antigens (HLA). 1,2 Srivastava et al. 3 have recently described high rates of false-positive hepatitis C antibody tests in LVAD patients, thereby supporting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…On the other hand, disappearance of anti‐HCV antibodies, in the case of CF‐LVADs particularly after removal of the device, would significantly increase the likelihood of these being false positive antibodies probably formed in a nonspecific immune response to CF‐LVAD biomaterial. In our study, we found that about 19% of all LVAD recipients developed anti‐HCV antibodies with concomitantly undetectable HCV‐RNA, which was in keeping with the incidences reported in prior studies . Upon repeat testing, we found that all of the positive HCV‐antibody tests turned negative.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…On the other hand, disappearance of anti‐HCV antibodies, in the case of CF‐LVADs particularly after removal of the device, would significantly increase the likelihood of these being false positive antibodies probably formed in a nonspecific immune response to CF‐LVAD biomaterial. In our study, we found that about 19% of all LVAD recipients developed anti‐HCV antibodies with concomitantly undetectable HCV‐RNA, which was in keeping with the incidences reported in prior studies . Upon repeat testing, we found that all of the positive HCV‐antibody tests turned negative.…”
Section: Discussionsupporting
confidence: 90%
“…According to the International Society of Heart and Lung Transplant (ISHLT) guidelines, a positive screening HCV‐antibody test must be followed by a confirmatory HCV‐RNA test before a potential candidate can be listed, with additional HCV testing as needed while wait listed, often prolonging wait list times . Over the years and for unclear reasons, formation of anti‐HCV antibodies in the absence of HCV‐RNA has been a fairly common occurrence in patients with CF‐LVADs with the reported incidences ranging from 16% to 59% . This phenomenon has thus far been attributed to the increased alloantibody synthesis seen with exposure of monocytes to LVAD‐derived biomaterial and as such, in the few cross‐sectional studies published so far, anti‐HCV antibodies formed in the absence of detectable HCV‐RNA in patients with CF‐LVADs have been deemed “false positive” …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations